Design and software implementation of solid state transformer - Raaed Faleh Hassan, Dr (International Journal of Engineering and Technology, 2018)
The work presented in this paper concerned with the analysis, design and software implementation of the Solid State Transformer as an alternative to the conventional power transformer. The proposed transformer aims to perform the same task as the conventional one with additional facilities and advantages. Three stages are considered to configure the Solid State Transformer. The first stage which is known as input stage and implemented using Vienna rectifier which converts the AC voltage of the main supply to a DC voltage. The second stage (isolation stage) step down the DC voltage to a lower level DC voltage. This stage consists of a single – phase five-level diode clamped inverter, 1 KHz step – down transformer and fully controlled bridge rectifier. The output stage (third stage) is a three-phase three-level diode clamped inverter which converts the low level DC voltage to a three-phase, 50 Hz AC voltage. Model Predictive Current Control has been employed for driving transformer’s stages. The gating signal is produced directly when the given cost function is minimized, therefore there is no need of any modulator. Behavior of the proposed structure is achieved by simulation which shows high quality power conversion with low Total Harmonic Distortion.
Keywords: Solid-State Transformer; Model Predictive Current Control; Vienna Rectifier; Diode Clamped Converter and High Frequency Transformer.